INTEGRATING AR AND AI FOR IMMERSIVE SCULPTURE EXHIBITIONS - J. Vijay; Jain, Romil; Guntaj J; Srinivasulu, Senduru; Todkari, Vinod Chandrakant; Srishti, Pooja (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The paper addresses the issue of combining Augmented Reality (AR) and Artificial Intelligence (AI) to create the experience of thicker and adaptive sculpture display that will change the interactions of the audience in the digital era. The proposed scheme outlines how AR technologies can be employed to add to physical sculptures some dynamic and interactive depth of information and sensory enhancement and AI will personalize these experiences to their current preferences of use behavior. The cognitive and emotional associations between visitors and artworks are deeper are formed with the help of the visual augmentation of the system along with clever content adaptation. The concept framework is based on experiential learning, aesthetic perception, and human-computer interaction theories to provide grounds on hybrid AR-AI exhibition environments. The research design used in the study involves a combination of qualitative interviews, observational analysis, and quantitative usability testing with the use of a mixed-methods research design. To create the prototype system, there are tools, including Unity 3D, ARCore, TensorFlow, and 3D scanning technologies. It is characterized by an AR interface that allows visualizing sculpture in real-time, AI algorithms that examine the behavior of users, and a feedback-based data pipeline that optimizes the system in the long run. The metrics to be evaluated are immersion, engagement, and learning outcomes which are assessed by user experience studies and comparison with traditional settings of exhibits.